Synthesis and lipid-lowering properties of novel N-(4-benzoylphenyl) pyrrole-2-carboxamide derivatives in Triton WR-1339-induced hyperlipidemic rats - Tariq Al-Qirim, Abdel Qader Al Bawab, Yusuf Al-Hiari, Nisreen Haj Ahmad, Mohammad Alwahsh, Sameer Al-Kouz, Ghassan Shattat (Journal of Applied Pharmaceutical Science, 2024)
One of the main risk factors that contribute to hyperlipidaemia is atherosclerosis and coronary heart disease. Therefore, researchers turn to synthesizing new compounds with potential lipid-lowering effects to overcome this issue. In the current study, Triton WR-1339 was used to induce hyperlipidaemia in the rat’s model. Moreover, we were able to synthesize, characterize, and validate a novel series of N-(4-benzoylphenyl) pyrrole-2-carboxamide derivatives; (compounds 3 and 5) and assess their potency as anti-hyperlipidemic agents. 300 mg/kg of triton WR-1339 was administered overnight intraperitoneally to fasted rats to urge hyperlipidemia and divided into five groups, control, hyperlipidemic, compounds 3-, 5-, and bezafibrate-treated rats. The pharmacological evaluation of compounds 3 and 5 at a dose of 15 mg/kg body weight showed that the elevated levels of plasma triglyceride, low-density lipoprotein cholesterol, and total cholesterol were significantly reduced after 18 hours of compounds 3 (p < 0.001) and compound 5 (p < 0.01) administration in comparison to the hyperlipidemic and control group at a given 15 mg/kg body weight dose. Moreover, it was noted that compounds 3 and 5 increased the high-density lipoproteins cholesterol levels significantly by 22% and 4.5% consecutively. Therefore, it can be concluded from these findings that N-(4-benzoylphenyl) pyrrole-2-carboxamide derivatives (3 and 5) have a definite antihyperlipidemic potential which could serve as protective agents against cardiovascular diseases and atherosclerosis.
Keywords: Pyrrole carboxamides, hypolipidemic activity, Triton WR-1339, rats